(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Pneumonia in children remains a serious public health problem, requiring the introduction of new approaches to diagnostics. Modern research emphasizes the importance of a combination of clinical, laboratory and radiological methods. According to the World Health Organization, millions of cases occur each year, especially among infants and young children. The persistent high level of morbidity and mortality determines the relevance of the problem.